2007
DOI: 10.1007/s10856-006-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of Sr2+ on the structure and reactivity of SrO–CaO–ZnO–SiO2 ionomer glasses

Abstract: The suitability of Glass Polyalkenoate Cements (GPCs) for use in orthopaedics is retarded by the presence in the glass phase of aluminium, a neurotoxin. Unfortunately, the aluminium ion plays an integral role in the setting process of GPCs and its absence is likely to hinder cement formation. However, the authors have previously shown that aluminium free GPCs may be formulated based on calcium zinc silicate glasses and these novel materials exhibit significant potential as hard tissue biomaterials. To further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 35 publications
2
53
0
Order By: Relevance
“…So, the addition of ZnO has a smaller disrupting effect on the structure and hence it will strengthen the network (31) . This result was in agreement with that of Boyd et al (32) who worked on a SrO-CaO-ZnO-SiO 2 glass ionomer composition and that of Abou Neel et al (33) who worked on Srdoped phosphate glasses.…”
Section: Water Solubility and Water Sorption Analysissupporting
confidence: 92%
“…So, the addition of ZnO has a smaller disrupting effect on the structure and hence it will strengthen the network (31) . This result was in agreement with that of Boyd et al (32) who worked on a SrO-CaO-ZnO-SiO 2 glass ionomer composition and that of Abou Neel et al (33) who worked on Srdoped phosphate glasses.…”
Section: Water Solubility and Water Sorption Analysissupporting
confidence: 92%
“…There are, however, limited studies on strontium-containing bioactive glass bone substitutes. The role of Sr on the structure and reactivity of dental ionomer glasses has been reported by Boyd et al [18]. Abou Neel et al [19] reported some structural and physical characteristics of melt-derived phosphate glasses based on Na 2 O-CaO-SrO-P 2 O 5 system.…”
Section: Discussionmentioning
confidence: 95%
“…, Sr 2? ) act predominantly as a network modifier within a glass structure [3,14], and this study aims to use complementary characterization techniques such as high resolution XPS, magic-angle spinning nuclear magnetic resonance (MAS-NMR) and Raman spectroscopy to investigate any structural differences within the glass as a result of Na ? and Sr 2?…”
Section: Introductionmentioning
confidence: 99%